IMPLEMENTASI NILAI PANCASILA DALAM KEHIDUPAN MAHASISWA PERTANIAN - Adelia, Habsah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This research aims to implement the application of Pancasila values ​​in academic and non-academic activities at the Faculty of Agriculture. As the basic ideology of the Indonesian nation, Pancasila plays an important role as a guide in various aspects of life, including higher education. At the Faculty of Agriculture, the application of Pancasila values ​​is reflected through mutual cooperation in laboratory and field activities, social justice in the distribution of tasks and research results, and strengthening a sense of nationalism through a curriculum that supports national food conservation. This research uses a qualitative approach with data collection methods through interviews, observation and document analysis. The results show that Pancasila values ​​have been implemented through community service programs, student activities, and the integration of these values ​​into the lecture curriculum. However, there are challenges in the form of a lack of individual awareness of the importance of Pancasila and limited facilities. Therefore, strategic steps are needed to increase understanding and application of Pancasila values ​​as a whole. It is hoped that this research can become a reference for higher education institutions in strengthening the application of Pancasila values ​​to produce graduates who are not only academically superior, but also have strong national character.